2021
DOI: 10.3389/fcimb.2021.678961
|View full text |Cite
|
Sign up to set email alerts
|

Localized Provoked Vulvodynia-An Ignored Vulvar Pain Syndrome

Abstract: Localized provoked vulvodynia (LPV) causes dyspareunia among reproductive aged women. We review the pathogenesis of LPV and suggest that LPV is an inflammatory pain syndrome of the vestibular mucosa triggered by microbial antigens in a susceptible host. Tissue inflammation and hyperinnervation are characteristic findings which explain symptoms and clinical signs. Education of health care providers of LPV is important since this condition is common, often unrecognized, and patients often become frustrated users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
1
2
Order By: Relevance
“…First, multiple studies suggest that inflammation may play a role in the development of PV. 5,28,61 The current result support this notion, indeed, we found that repeated inflammation led to long-lasting mechanical and thermal vulvar hypersensitivity. However, in the current study we focused only on inflammation in the development of PV, and this a limitation of the current study.…”
Section: Dovepresssupporting
confidence: 88%
See 1 more Smart Citation
“…First, multiple studies suggest that inflammation may play a role in the development of PV. 5,28,61 The current result support this notion, indeed, we found that repeated inflammation led to long-lasting mechanical and thermal vulvar hypersensitivity. However, in the current study we focused only on inflammation in the development of PV, and this a limitation of the current study.…”
Section: Dovepresssupporting
confidence: 88%
“…26,27 Hyperinnervation and mast cells (MCs) accumulation in the vulva among PV has led to the hypothesis that early inflammatory events set the stage for longterm MC increase in the vulva, which in turn supports the overgrowth of the sensory neurons at the early stage of the inflammation, as well as the stability of the hyperinnervation of neurons after the inflammation subsides. 14,26,28 However, whether mast cell-mediated inflammation can drive hyperinnervation and neuromodulation manifests in vulvar allodynia, and hyperalgesia remains unknown. Here, we investigated the long-term effects of inflammation on vulvar sensitivity, local inflammatory changes, and the role of mast cells in the development of chronic vulvar sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the patients with LPV were more likely to have Candida compared with the controls. Notably, other studies have reported a link between a history of vulvovaginal candidiasis outbreaks and the onset of LPV symptoms 31–33 . In addition, we found no significant difference in the presence of GBS between the 2 groups.…”
Section: Discussioncontrasting
confidence: 57%
“…Notably, other studies have reported a link between a history of vulvovaginal candidiasis outbreaks and the onset of LPV symptoms. [31][32][33] In addition, we found no significant difference in the presence of GBS between the 2 groups. This is in disagreement with some studies that have shown an increase in the prevalence of certain strains of streptococci in women with LPV.…”
Section: Discussioncontrasting
confidence: 50%